Gender, household and individual income in France, Germany, Italy, the Netherlands, Sweden, the USA and the UK - Katherine Rake; Mary Daly (Luxembourg Income Study (LIS), 2002)
This paper examines gender differentials in the resources of households and individuals across seven welfare states. In its first part, it asks whether female-headed households can secure a living income without recourse to either the state or the income of a male partner. It then steps inside the private sphere, for the purpose of investigating gender differentials in individual incomes and the degree to which women and men rely on the family as a source of financial support. Technical details of the methodology employed for this analysis follow in an appendix.
Keywords: 330; Geschlecht; Haushaltseinkommen; Einkommen; Vergleich; USA; Großbritannien; Deutschland; Frankreich; Schweden; Italien; Niederlande; Geschlechterforschung